Pengaruh Model Problem Based Learning Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 4 Laguboti Tahun Pembelajaran 2023/2024” Skripsi: Jurusan Pendidikan Agama Kristen Institut Agama Kristen Negeri Tarutung - Juni Hastuti Harianja; Johari Manik; Ordekoria Saragih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study was to determine the effect of the Problem Based Learning model on the learning activity of Christian Religious Education of class VIII students of SMP Negeri 4 Laguboti in the 2023/2024 Academic Year. The method used in this study is a descriptive quantitative research method with an inferential statistical approach. The population is all class VIII students of SMP Negeri 4 Laguboti in the 2023/2024 Academic Year who are Christian, totaling 164 people and a sample of 49 people is determined, which is 30% of the population using the simple random sampling technique. Data were collected using a positive closed questionnaire of 33 items. The results of the data analysis show that there is an influence of the Problem Based Learning model on the learning activity of Christian Religious Education of class VIII students of SMP Negeri 4 Laguboti in the 2023/2024 Academic Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.682> rtable ( = 0.05, n = 49) = 0.281 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 6.397> ttable ( = 0.05, dk = n-2 = 47) = 2.021 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂=